CA125 outperforms NT-proBNP in acute heart failure with severe tricuspid regurgitation. (1st June 2020) - Soler, Meritxell; Miñana, Gema; Santas, Enrique; Núñez, Eduardo; de la Espriella, Rafael; Valero, Ernesto; Bodí, Vicente; Chorro, Francisco J.; Fernández-Cisnal, Agustin; D'Ascoli, Giulio; Marti-Cervera, Jorge; Sanchis, Juan; et al.
Abstract: Background: In acute heart failure (AHF) with right ventricular dysfunction, the roles of amino-terminal pro-brain natriuretic peptide (NT-proBNP) and carbohydrate antigen 125 (CA125) are poorly understood, and functional tricuspid regurgitation (TR) severity is thought to indicate a poor prognosis. We examined the prognostic abilities of NT-proBNP and CA125 according to TR status among patients with AHF. Methods: TR severity was assessed during index hospitalization (108 ± 24 h after admission) and classified as none/trivial, mild, moderate, or severe. Multivariable Cox regression analysis was performed to assess how pre-discharge CA125 and NT-proBNP were associated with long-term all-cause mortality relative to TR severity. Results: We prospectively included 2961 patients discharged following hospitalization for AHF (mean age 74 ± 11 years; 49.0% women; 51.8% with left ventricular ejection fraction >50%). Median NT-proBNP was 4823 ng/L (IQR: 2086–9183) and CA125 was 58.1 U/mL (IQR: 25–129). Severe TR was present in 300 patients (10.1%), and 1821 patients (61.5%) died (mean follow-up, 3.3 ± 3.2 years). Multivariate analysis revealed a differential prognostic effect across TR status for both biomarkers ( p -value for both interactions<0.05). NT-proBNP was significantly linearly associated with mortality in non-severe TR ( p < 0.001), but not in severe TR ( p = 0.308). Higher CA125 values were significantly associated with mortality risk in all patients (HR: 1.09; 95% CI:1.03–1.14; p = 0.001), with a greater effect in those with severe TR (HR: 1.28; 98% CI:1.11–1.48; p = 0.001). Conclusions: In patients with AHF and severe TR, CA125 outperforms NT-proBNP in predicting long-term mortality. In AHF with right ventricular involvement, CA125 may be the preferred biomarker for risk stratification. Graphical abstract: Unlabelled Image Highlights: The severity of TR influenced the value of NT-proBNP for risk stratification in patients with acute heart failure. NT-proBNP was not associated with the risk of mortality when severe TR was present. CA125 was a robust predictor of long-term mortality in patients with severe TR. CA125 outperforms NT-proBNP in predicting long-term mortality in patients with acute heart failure and severe TR.